Acute effect of a long-distance road competition on foot strike patterns, inversion and kinematics parameters in endurance runners - Latorre-Roman, P. A.; Jimenez, M. M.; Soto Hermoso, V. M.; Salas Sanchez, J.; Molina Molina, A.; Robles Fuentes, A.; Garcia-Pinillos, F. (International Journal of Performance Analysis in Sport, 2015)
The purpose of this study was to determine the foot strike patterns, inversion and kinematics variables in recreational runners during a long-distance road competition, determining an association between foot strike pattern's classification, inversion and kinematics variables with athletic performance and sex. Five hundred and forty-two athletes who participated in a half marathon passed through the 15 km data collection point. Photogrammetric techniques (2D) were used to measure contact time and flight time. A high prevalence of rearfoot and high rearfoot strikes was found among the most recreational distance runners. No significant differences between sexes in foot strike pattern were found, whilst significant differences between level groups in the asymmetry (first level = 96.5%, second level = 10.6% and third level = 0.4%) were found. Additionally, forefoot and high forefoot strike exhibit greater percentage for inversion. Moreover, athletes with high rearfoot and rearfoot strike showed a greater contact time and lower flight time. Foot strike patterns were influenced by running speed; thus, athletes with higher performance exhibit lower frequency of rearfoot and high rearfoot strikes. Further research could clarify the causes and consequences (performance and injury) of the current findings.